Associations between reasons for vaping and current vaping and smoking status: Evidence from a UK based cohort. (1st December 2020) - Khouja, Jasmine N.; Taylor, Amy E.; Munafò, Marcus R.
Highlights: Reasons for vaping are associated with vaping and smoking status in UK young adults. Vaping out of curiosity and to quit smoking is popular in this population. Vaping out of curiosity is associated with discontinued vaping. Vaping to stop smoking is associated with quitting smoking. Vaping to cut down smoking does not appear to encourage quitting. Abstract: Background: This study aimed to discover which young adults vape, the reasons given for vaping, and which reasons for vaping are associated with continued vaping/smoking. Methods: In a UK cohort of 3, 994 young adults, we explored the association of retrospectively-recalled reasons for vaping by 23 years (collected between 2015 and 2016) with vaping/smoking status at 24 years (collected between 2016 and 2017). Using logistic regression, we assessed the association with vaping behaviour among ever vapers who had ever smoked (n = 668), and with smoking behaviour among individuals who regularly smoked prior to vaping (n = 412). Results: Vaping to quit smoking was associated with higher likelihood of vaping (odds ratio [OR] = 3.51, 95 % confidence interval [95 % CI] = 2.29–5.38), but lower likelihood of smoking at 24 years (OR = 0.50, 95 %CI = 0.32 to 0.78). Vaping to cut down smoking was associated with higher likelihood of vaping (OR = 2.90, 95 % CI = 1.87–4.50) and smoking at 24 years (OR = 1.62, 95 % CI = 1.02–2.58). Vaping out of curiosity was associated with lower likelihood of vaping at 24 years (OR = 0.41, 95 %CI = 0.26 to 0.63) but higher likelihood of smoking at 24 years (OR = 1.66, 95 % CI = 1.04–2.65). Conclusions: Intention to quit appears important for young adults to stop smoking using e-cigarettes. Public health strategies that encourage vaping specifically for smoking cessation may encourage quitting among young adults.